1964
DOI: 10.1073/pnas.51.3.407
|View full text |Cite
|
Sign up to set email alerts
|

Templates for the First Proteins of Embryonic Development

Abstract: The gathering strength of the messenger hypothesis,' and accumulating evidence in favor of polyribosomes as the sites of protein synthesis,2 are exerting strong influence on current research in chemical embryology. The scheme now generally accepted for microorganisms and certain mammalian cells" 2 provides a number of specific mechanisms by which cellular differentiation could be initiated and controlled. Their essential feature is a direct genomic regulation of the spectrum of proteins made in different cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1966
1966
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Translational control of protein expression is a phenomenon known from other organisms, most notably the sea urchin in its early embryonic development (Gross et al, 1964), where the overall rate of protein synthesis increases after fertilization (Brandhorst, 1976). Examples of a more selective type of translational control have been reported to occur in higher organisms (Shull & Theil, 1982;Maundrell et al, 1983;McGuire et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Translational control of protein expression is a phenomenon known from other organisms, most notably the sea urchin in its early embryonic development (Gross et al, 1964), where the overall rate of protein synthesis increases after fertilization (Brandhorst, 1976). Examples of a more selective type of translational control have been reported to occur in higher organisms (Shull & Theil, 1982;Maundrell et al, 1983;McGuire et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the level of a transcript required for mitosis in Aspergillus nidulans (nimA) has been found to be cell-cycle regulated (14). Selective translation of preexisting mRNA can also control the onset of meiosis as seen in many embryo systems (15)(16)(17). Our finding of multiple mitotic events in mammalian cells is related to earlier experiments conducted with cycloheximide-treated Xenopus eggs, in which repeated injections of maturation promoting factors followed by their spontaneous inactivation repeatedly induced mitosis and subsequent return to interphase (18).…”
Section: Discussionmentioning
confidence: 99%
“…while the ribosomes are saturated with old m-RNA. Further evidence that m-RNA molecules may exist within the cell that do not take part in protein synthesis is provided by the experiments of Gross, Malkin & Moyer (1964) and Gross & Cousineau (1963). They showed that incorporation of labelled amino acids into proteins of fertilized sea-urchin eggs continues for 7 hr.…”
Section: Resultsmentioning
confidence: 81%